Recently created man-made habitats in Doñana provide alternative wintering space for the threatened Continental European black-tailed godwit population - Márquez-Ferrando, R.; Figuerola, J.; Hooijmeijer, J.C.E.W.; Piersma, T. (Biological Conservation, 2014)
Over the last decades the Continental European population of black-tailed godwits, Limosa limosa limosa, has shown steep declines as a consequence of agricultural intensification on the breeding grounds. Although numbers have also declined in their traditional wintering areas in West-Africa, in the Donana wetlands of southwestern Spain high nonbreeding numbers have persisted. Here we provide a long-term (35 year, 1977-2011) analysis of godwit numbers in Donana. In fact, from the mid 1990s there has been a steep increase in numbers so that the fraction of godwits along this flyway that winters in Donana increased from 4% in the late 1980s to 23% in 2011. These changes were not correlated with climatic conditions in Spain, nor in Sahel, but they were associated with changes in habitat availability - mainly an increase in man-made artificial wetlands. Commercial fish-farms and rice fields provide alternative habitats to the original seasonal marshlands for daytime roosting (mainly in the fish ponds) or nocturnal foraging (probably rice fields in addition to fish ponds). For migrating waterbirds, degradations of natural wetlands can thus be compensated by man-made alternative habitats. As the availability especially of such man-made areas is highly sensitive to short-term political/economic driven decision-making, they should be given greater consideration in global conservation plans.